Correlations between secondary structure- and protein–protein interface-mimicry: the interface mimicry hypothesis. Issue 12 (8th March 2019) - Taechalertpaisarn, Jaru; Lyu, Rui-Liang; Arancillo, Maritess; Lin, Chen-Ming; Perez, Lisa M.; Ioerger, Thomas R.; Burgess, Kevin
Abstract : Preferred conformations of several peptidomimetics (specifically, minimalist mimics ) were elucidated and compared with protein-protein interfaces on a huge scale, leading to a hypothesis regarding how these compounds mimic protein interface segments. Abstract : An active segment of the research community designing small molecules ("minimalist mimics" of peptide fragments) to interfere with protein–protein interactions have based their studies on an implicit hypothesis. Here we refer to this as the Secondary Structure Hypothesis, that might be defined as, "If a small molecule can orient amino acid side-chains in directions that resemble side-chains of the parent secondary structure at the interface, then that small molecule is a candidate to perturb the protein–protein interaction". Rigorous tests of this hypothesis require co-crystallization of minimalist mimics with protein receptors, and comparison of the bound conformations with the interface secondary structures they were designed to resemble. Unfortunately, to the best of our knowledge, there is no such analysis in the literature, and it is unlikely that enough examples will emerge in the near future to test the hypothesis. Research described here was designed to challenge this hypothesis from a different perspective. In a previous study, preferred conformations of a series of novel minimalist mimics were simulated then systematically overlaid on >240 000 crystallographically characterized protein–protein interfaces. Select data from that overlay procedure revealed chemotypes that overlay side chains on various PPI interfaces with a relatively high frequency of occurrence. The first aim of this work was to determine if good secondary structure mimics overlay frequently on PPI interfaces. The second aim of this work was to determine if overlays of preferred conformers at interface regions involve secondary structures. Thus situations where these conformations overlaid extremely well on PPI interfaces were analyzed to determine if secondary structures featured the PPI regions where these molecules overlaid in the previous study. Combining conclusions from these two studies enabled us to formulate a hypothesis that is complementary to the Secondary Structure Hypothesis, but, unlike this, is supported by abundant data. We call this the Interface Mimicry Hypothesis.